Telaah Kritis Pasal 7 Undang-Undang No.16 Tahun 2019 Tentang Perkawinan - Elfirda Ade Putri (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2021)
Marriage is also regulated in Article 28B Paragraph 1 of the 1945 Constitution which states